Asymmetric Price Adjustment in the Small - Haipeng (Allan) Chen; Daniel Levy; Sourav Ray; Mark Bergen (Journal of Monetary Economics, 2008)
Analyses of a large retail scanner price data set reveal a new and surprising regularity – small price increases occur more frequently than small price decreases for price changes of up to 10. That is, we find asymmetric price adjustment “in the small.” Furthermore, it turns out that inflation offers only a partial explanation for the finding. Indeed, substantial proportion of the asymmetry remains unexplained, even after accounting for the inflation. For example, the asymmetry holds also after excluding periods of inflation from the data, and even for products whose price had not increased. The findings hold for different aggregate and disaggregate measures of inflation and also after allowing for lagged price adjustments.
Keywords: E31; D11; D21; D80; L11; L16; M31; 330; Asymmetric Price Adjustment; Price Rigidity; Inflation; Rational Inattention; Monetary Policy